2017
DOI: 10.1111/grs.12176
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq of Agropyron mongolicum Keng in response to drought stress

Abstract: Agropyron mongolicum Keng is the predominant perennial forage crop in the steppes of the Inner Mongolian Plateau, China. It is known to be tolerant to drought, low temperature and salinity, and is also a valuable resource for wheat improvement. However, the corresponding molecular mechanism underlying the adaptation to water shortage in A. mongolicum remains uncharacterized. In this study, the molecular responses of A. mongolicum were compared during drought stress. Two libraries prepared from control and drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…In total, 262,427,357 high-quality sequencing reads were assembled into 76,601 contigs, and a total of 72,474 transcripts were generated by the program CD-HIT-EST (Tables 1 and S2 ). The average length of 803 bp and N50 of 1,377 bp are comparable to the results from other de novo transcriptome assemblies [ 24 29 ]. BLASTx results were obtained for 45.6% transcripts against S .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In total, 262,427,357 high-quality sequencing reads were assembled into 76,601 contigs, and a total of 72,474 transcripts were generated by the program CD-HIT-EST (Tables 1 and S2 ). The average length of 803 bp and N50 of 1,377 bp are comparable to the results from other de novo transcriptome assemblies [ 24 29 ]. BLASTx results were obtained for 45.6% transcripts against S .…”
Section: Discussionsupporting
confidence: 79%
“…Abscisic acid is known as a major hormone playing crucial roles in abiotic stress responses by inducing stomatal closure and regulating gene expression [ 52 ]. Previous studies have shown that many genes involved in ABA biosynthesis and signaling were upregulated under water deficit [ 28 , 29 , 53 , 54 ]. A rate-limiting enzyme in ABA biosynthesis was induced and its expression level was gradually increased as dehydration prolonged in pear [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results reported here do indicate that genetic variation between the three genotypes has significant and measurable impacts on patterns of gene expression in response to water stress. The fact that such variation should exist is not surprising and there are numerous examples of gene-expression studies and QTL analyses for different aspects of drought tolerance in forage and other grasses (e.g., Alm et al, 2011 ; Merewitz et al, 2014 ; Baldoni et al, 2016 ; Jiang et al, 2017 ; Liang et al, 2017 ; Zhu et al, 2017 ; Cheruiyot et al, 2018 ; Hu et al, 2018 ; Ji et al, 2018 ; Kumar et al, 2018 ; Ling et al, 2018 ; Ma et al, 2018 ; Chaichi et al, 2019 ; Dinkins et al, 2019 ; Fradera-Sola et al, 2019 ). However, in the context of Brachiaria breeding, these genotypes were selected from a cultivar development program and the results suggest selectable variation with measurable impacts.…”
Section: Discussionmentioning
confidence: 99%
“…MwAP2/EREBP, isolated through RT-PCR and RACE techniques, demonstrated its involvement in drought-tolerance in A. mongolicum Keng [8]. Recently, Ma and associates have identified and evaluated drought-responsive RNAs through transcriptome analysis in A. mongolicum [9]. However, to date to the best of our knowledge, no experimentally or computationally identified drought-responsive miRNAs in A. mongolicum have been reported.…”
Section: Introductionmentioning
confidence: 99%